History of facial reconstruction - Verzé, L. (Acta Biomedica Atenei Parmensis, 2009)
We briefly describe the history of facial reconstruction in the deceased, starting from the skull. Facial reconstruction has passed through many phases and has been variously motivated, from religion and ancestor worship, through anthropology, to the identification of lost persons for forensic purposes. Renaissance artists used this technique for modelling and teaching. Techniques changed over the centuries but the ultimate goal was to create a convincing likeness of the dead. The two current activities are forensic facial reconstruction and reconstructing the personal appearance of ancient people.